Penggusuran di Jakarta dalam Bingkai Etika Utilitarianisme - Hamudy, Nurul Annisa (Jurnal Bina Praja, 2019)
DKI Jakarta Government’s eviction policy is often considered to be wrong or has a negative image (even violating the Human Rights) because eviction is synonymous with riot, coercion, expulsion, and always ends in conflict. Although according to the utilitarianism philosophy, no actions, including evictions, are inherently wrong. All actions or regulations by itself are neutral. What gives moral values to actions or regulations are its consequences. The objective of this study was to determine the positive consequences of eviction actions by using the philosophical perspective of Utilitarianism. The study used descriptive and literature review methods, as well as qualitative approach, the results of the study showed that eviction policies were justified in the utilitarian view, Eviction of a handful of residents living on the riverbanks was done to normalize the riverbank and green areas to save millions of DKI Jakarta residents from floods. The main objective of the eviction was the public interest. Therefore, evictions must be conducted for the greater good, benefiting as many people as possible and carried out in ways that humanize people.